Egyptian personal piety and Israel's wisdom literature - S. Fischer (Acta Theologica)
This article evaluates the movement of Egyptian personal piety and its relation to Israelite wisdom texts. Hymns and prayers of personal piety developed in the New Kingdom at the same time as “heretic” Harpers’ songs and love songs. The personal piety affected also the genre of instructions. The instruction of Amenemope had not only a literary effect on “The Words of the Wise” but also a theological impact on its view of god. Amenemope and Qoheleth agree in the acknowledgement of a god with an awesome power but Qoheleth doesn’t develop a personal piety. The hymns of personal piety didn’t have an independent effect on Qoheleth. The hymns of personal piety share vocabulary and motifs with the Egyptian love songs, which in turn had an effect on Song of Songs. An acquaintance of Song of Songs with texts of personal piety outside of Egyptian love songs did not exist.